A Study of Reverse-Worded Matched Item Pairs Using the Generalized Partial Credit and Nominal Response Models - Matlock, Ki Lynn (Educ Psychol Meas, 2016)
The generalized partial credit model (GPCM) is often used for polytomous data; however, the nominal response model (NRM) allows for the investigation of how adjacent categories may discriminate differently when items are positively or negatively worded. Ten items from three different self-reported scales were used (anxiety, depression, and perceived stress), and authors wrote an additional item worded in the opposite direction to pair with each original item. Sets of the original and reverse-worded items were administered, and responses were analyzed using the two models. The NRM fit significantly better than the GPCM, and it was able to detect category responses that may not function well. Positively worded items tended to be more discriminating than negatively worded items. For the depression scale, category boundary locations tended to have a larger range for the positively worded items than for the negatively worded items from both models. Some pairs of items functioned comparably when reverse-worded, but others did not. If an examinee responds in an extreme category to an item, the same examinee is not necessarily likely to respond in an extreme category at the opposite end of the rating scale to a similar item worded in the opposite direction. Results of this study may support the use of scales composed of items worded in the same direction, and particularly in the positive direction.